2022
DOI: 10.3393/ac.2021.00017.0002
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after endoscopic resection of small rectal neuroendocrine tumors: a retrospective cohort study

Abstract: According to the European Neuroendocrine Tumor Society consensus guidelines, rectal neuroendocrine tumors (NETs) up to 10 mm in size and without poor prognostic factors could be safely removed with endoscopic resection, suggesting omitting surveillance colonoscopy after complete resection. However, the benefit of surveillance colonoscopy is still unknown. In this study, we aimed to report the outcomes after endoscopic resection of small rectal NETs using our surveillance protocol. Methods: This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Similarly, Pattarajierapan et al. also found that 2.2% of rectal NET patients with positive margins had no recurrence ( 18 ). Li et al.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Pattarajierapan et al. also found that 2.2% of rectal NET patients with positive margins had no recurrence ( 18 ). Li et al.…”
Section: Discussionmentioning
confidence: 94%